2018
DOI: 10.1186/s12936-018-2255-z
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of intermittent preventive treatment and pregnancy outcomes: health facilities and community surveys in Chókwè district, southern Mozambique

Abstract: BackgroundMalaria in pregnancy leads to serious adverse effects on the mother and the child and accounts for 75,000–200,000 infant deaths every year. Currently, the World Health Organization recommends intermittent preventive treatment of malaria in pregnancy (IPTp) with sulfadoxine–pyrimethamine (SP) at each scheduled antenatal care (ANC) visit. This study aimed to assess IPTp-SP coverage in mothers delivering in health facilities and at the community. In addition, factors associated with low IPTp-SP uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 49 publications
13
26
2
Order By: Relevance
“…This was mainly linked to late and infrequent ANC attendance, which led to missed opportunities for the provision of the recommended IPTp-SP dosage. This is in agreement with our previously reported results in the study on IPTp-SP coverage among delivering women conducted in the same setting [17]. Similar studies conducted in Uganda and Mali also found that late and infrequent ANC attendance were important factors influencing poor uptake of IPTp-SP and other malaria preventive measures [23,24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was mainly linked to late and infrequent ANC attendance, which led to missed opportunities for the provision of the recommended IPTp-SP dosage. This is in agreement with our previously reported results in the study on IPTp-SP coverage among delivering women conducted in the same setting [17]. Similar studies conducted in Uganda and Mali also found that late and infrequent ANC attendance were important factors influencing poor uptake of IPTp-SP and other malaria preventive measures [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…The semi-structured interviews with pregnant women and health workers provided useful information on the perceived gaps that challenges the uptake of IPTp-SP among pregnant women. The qualitative data supports quantitative findings from the study on IPTp-SP coverage among delivering women, that was undertaken in parallel to this study, reported similarly low levels of awareness and knowledge of IPTp services among pregnant women in the same area [17].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…, 11 from Ethiopia[52][53][54][55][56][57][58][59][60][61][62][63], 6 from Kenya[5,54,[64][65][66][67], 7 from Malawi [4, 6, 68-72], 3 from Sudan [10, 73, 74], 3 from Zambia [75-77],3 from Zimbabwe [78-80], 2 from Uganda [7, 81], 2 from Mozambique[82,83], 1 from Rwanda[84], and 1 from Madagascar[85]. Twenty five studies were done by cohort study design[33, 35, 36, 39, 41, 43, 45-50, 59, 61, 65-68, 70, 75, 77, 80, 83-85], 9 studies by case control study design[7,10,37,38,53,55,57,73,79] and 24 studies by cross sectional study design[4-6, 34, 40, 42, 44, 51, 52, 54, 56, 58, 60, 62, 64, 69, 71, 72, 74, 76, 78, 81, 82] (Table 1).…”
mentioning
confidence: 99%
“…Studies reported from Ghana indicate that coverage of IPTp3+ is 46.6% in Tema metropolis of the Greater Accra region [39], 31.8% in Kumasi [50] and in Osu Klottey sub-district of Accra Metropolitan is 73.8% [51]. A study conducted in Chókwè district, southern Mozambique showed that coverage of three or more doses of SP is 46.6% [52]. It should be noted that Uganda, Ghana and Mozambique adopted the updated WHO IPTp policy in 2014, 2012 and 2014 respectively [53].…”
Section: Discussionmentioning
confidence: 99%